Effects of different cold-resistant agents and application methods on yield and cold-resistance of machine-transplanted early rice - Yuan, Shuai; Qin, Shiqi; Shi, Quan; Chen, Pingping; Tu, Naimei; Zhou, Wenxin; Yi, Zhenxie (Frontiers in Plant Science, 2024)
Cold stress is a critical factor affecting rice production worldwide. The application of cold-resistant agents may improve the cold resistance and yield of crops. To screen for suitable cold-resistant agents for machine-transplanted early rice, the effects of uniconazole, abscisic acid, and zinc-amino acids chelate and their spraying times (seed soaking stage, one leaf and one heart stage, two leaves and one heart stage, 7 days before the transplanting stage, and regreening stage) on the yield and cold resistance of machine-transplanted early rice were investigated. Moreover, the application method (spraying amount: 750 and 1125 g ha -1 ; spraying time: 7 days before the transplanting stage, transplanting stage, regreening stage, and transplanting stage and regreening stage) for the most suitable cold-resistant agent was optimized. The zinc-amino acids chelate was better than the other two cold-resistant agents for promoting rice tillering and increasing the leaf area index, dry matter weight, antioxidant enzyme activities (CAT, SOD, POD) and yield (i.e., 9.22% and 7.14% higher than uniconazole and abscisic acid, respectively), especially when it was applied in the regreening stage. The examination of spraying amounts and times indicated that the zinc-amino acids chelate dosage had no significant effect on the yield and cold resistance of early rice.However, the rice yield and antioxidant enzyme activities were highest when samples were sprayed once in the transplanting stage and the regreening stage. On the basis of the study results, 750 g ha -1 zinc-amino acids chelate applications in the transplanting and regreening stages of machine-transplanted early rice plants may be ideal for increasing cold stress resistance and yield.